LINGUISTIC EXPRESSION OF FIGURATIVE THOUGHT IN COGNITIVE LINGUISTICS - Qurbonova Kamola Abdurahmonovna (International Journal of Literature and Language Studies, 2026)
This article examines the linguistic expression of figurative thought from the perspective of cognitive linguistics. It discusses how conceptual metaphor, conceptual metonymy, image schemas, and other cognitive mechanisms are reflected in linguistic expressions. The study also explores the role of figurative thought in meaning construction, conceptualization, and human perception of reality. The findings indicate that figurative thought is a fundamental cognitive mechanism that explains the interaction between language, thought, and semantic representation.